Konsep Ekosufisme: Harmoni Tuhan, Alam Dan Manusia Dalam Pandangan Seyyed Hossein Nasr - Anggraini, Reni Dian; Rohmatika, Ratu Vina (AL-ADYAN, 2021)
This paper explains and describes how to analyze the concept of ecosufism: the harmony of God, nature and humans in the view of Seyyed Hossein Nasr. Nasr's concept of ecosufism started when he saw that humans were hit by a spiritual crisis that had an impact on the surrounding environment. So that the lack of spiritual value in humans makes an environmental crisis. Therefore, Nasr offers a teaching on how humans should be ethical and take care of nature properly in the form of issuing the concept of ecosufism. So that in the form of the ecosufism movement, it will create a harmony between God, nature and humans. In order to create peace and harmony with nature, humans must first submit and obey God's commands. In this discussion the author uses the library method by using various related sources in the form of books, journals and articles. Thus, this paper tries to explain how the concept of ecosufism pioneered by Seyyed Hossein Nasr and how the harmony of God, nature and humans.